2013
DOI: 10.1111/his.12164
|View full text |Cite
|
Sign up to set email alerts
|

The role of glutamate decarboxylase 65 in gastric cancer development, progression, and prognosis

Abstract: Our findings indicate that GAD65 is involved in the development and progression of gastric cancer as a tumour oncoprotein. Further elucidation of the molecular mechanisms underlying the role of GAD65 is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…That only few other tumor entities contained (weakly) GAD2-positive cases in <10% of cases fit well with the summarized data from the The Cancer Genome Atlas database where only very few nonpancreatic neoplasms displayed detectable but very low-level GAD2 RNA expression ( https://www.proteinatlas.org/ENSG00000136750-GAD2/summary/rna ). It is of note that other authors have described immunohistochemical GAD2 positivity in 71% of 313 gastric cancers, 12 55% of 108 adenocarcinomas of the gallbladder, 13 and in 30% of 46 parathyroidal adenomas. 13 However, GAD2 immunostaining was only observed in 1 (0.2%) of 467 gastric and 1 (2%) of 49 gallbladder adenocarcinomas.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…That only few other tumor entities contained (weakly) GAD2-positive cases in <10% of cases fit well with the summarized data from the The Cancer Genome Atlas database where only very few nonpancreatic neoplasms displayed detectable but very low-level GAD2 RNA expression ( https://www.proteinatlas.org/ENSG00000136750-GAD2/summary/rna ). It is of note that other authors have described immunohistochemical GAD2 positivity in 71% of 313 gastric cancers, 12 55% of 108 adenocarcinomas of the gallbladder, 13 and in 30% of 46 parathyroidal adenomas. 13 However, GAD2 immunostaining was only observed in 1 (0.2%) of 467 gastric and 1 (2%) of 49 gallbladder adenocarcinomas.…”
Section: Discussionmentioning
confidence: 79%
“…Only a few authors have examined GAD2 expression in cancer and proposed a role for tumor progression in gastric and gallbladder cancer. Song et al 12 reported a significantly higher GAD65 expression in 313 gastric cancers than in 60 adjacent nontumor tissues and found a link between high expression and the depth of tumor invasion, high TNM stage, and poor prognosis. For gallbladder adenocarcinoma, Deng and Pei 13 found increased levels of GAD65 immunostaining as compared with peritumoral tissues and a significant link between high GAD65 expression and reduced patient survival.…”
mentioning
confidence: 99%
“…The expression levels of GAD65 significantly correlate with the depth of tumor invasion and advanced TNM stage in gastric cancer and thus may be useful for reclassifying tumor growth patterns (9). In a clinicopathological study of benign and malignant lesions in the gallbladder, the expression level of GAD65 was significantly higher in the gallbladder adenocarcinoma than in the peritumoral tissues, adenomatous polyps, or areas of chronic cholecystitis.…”
Section: Discussionmentioning
confidence: 99%